Sultan Jawara Study Of The Bantenan Type From The Perspective Of Civil Law And Sharia - Faridatul Fauziah; Muchammad Fauzan Mujkhlis (LP2M IAIN Palopo, 2025)
The distribution of inheritance according to the Baduy indigenous community, both the outer Baduy and inner Baduy, prioritizes the kinship system and deliberation in the sociological approach of tribal structures between groups in kinship approaches to the patrilineal, matrilineal, and parental systems by maintaining the rights of the traditional customs of their communities which are carried out repeatedly in legal events which are made into legal rules that cannot be violated and do not violate the provisions stipulated by the state and this is protected by EX article 11 of the 1945 Constitution (Law no. 1 1974 Jo Law No. 16 of 2019 concerning marriage Chapter inheritance) while in Islamic law it has been standardized in verses 7, 11, 12 and 176 of the An-Nissa letter, but in the case of disputes, the element of deliberation with the heirs is prioritized.